Training on Cultivating Javanese Culture-Based Peace Values: Improving Teachers' Peace Competence at Al Akhlakul Karimah Foundation Sentolo Kulon Progo - Halqim, Afanin; Eliasa, Eva Imania; Lidyasari, Aprilia Tina; Rolina, Nelva; Anggito, Albi (Lembaga Penelitian dan Pengembangan Teknologi dan Rekayasa, Yayasan Ahmar Cendekia Indonesia, 2024)
This service project intends to help instructors at the Al Akhlakul Karimah Foundation gain insight into and absorb the virtues of the notion of peace in Javanese culture. The activity was carried out by administering a pretest questionnaire before to the distribution of content by experts and a posttest questionnaire following material exposure. Using the SPSS program, the pretest and posttest questionnaires were examined for homogeneity, normality, and t-tests. Foundation instructors are developing a better awareness of peace ideals. This is known based on the t test findings, which have a significance level of 0.010, indicating that there is an effect on teacher understanding before and after the test. The value of peace is essential to kids because it influences their conduct and character. At the Al-Akhlakul Karimah Sentolo foundation, Javanese culture-based training improved instructors' comprehension, which is intended to be used in the learning process to build students' character.